ДЕЯКІ АСПЕКТИ ПРИВАТИЗАЦІЇ ПІДПРИЄМСТВ ВУГІЛЬНОЇ ПРОМИСЛОВОСТІ: ЕКОНОМІКО-ПРАВОВИЙ АНАЛІЗ - Okhrimenko, Z.O. (Економіка та право, 2013)
The article presents a critical analysis of the current state and the main problems of legal regulation of privatization of the coal-mining enterprises of Ukraine. Some ways of solving the problematic issues are offered. REFERENCES: